Kelayakan Investasi Mesin Heat Exchanger pada PT LMN Kabupaten Bandung, Jawa Barat - Mufid, Iqbal Naufal; Wulandari, Eliana (Universitas Galuh, 2024)
Indonesia is one of the largest tea exporters in the world. One of tea products is green tea that is targeted for the European consumer. Currently, Indonesian tea producers faced regulations on Maximum Residue Level set by the European Union Commission regarding the maximum limit of anthraquinone compounds in tea, which was set at 0.02 mg/kg. Regarding this issue, PT LMN, as a green tea exporter, decided to invest in a heat exchanger to minimize anthraquinone contamination. This research aims to evaluate the financial feasibility of investing in a heat exchanger at PT LMN. This study uses a quantitative design with descriptive analysis technique. The financial feasibility analysis indicated that the investment was feasible, because the Net Present Value was greater than 0. Net Benefit Cost Ratio more than 1. Internal Rate of Return is greater than the discount rate, which is 10%, Payback Period is faster than project's lifespan, and Return on Investment shows a positive value.